Defining liveness - Alpern, Bowen
A formal definition for liveness properties is proposed. It is argued that this definition captures the intuition that liveness properties stipulate that 'something good' eventually happens during execution. A topological characterization of safety and liveness is given. Every property is shown to be the intersection of a safety property and a liveness property.